(untitled) (Світ фінансів, 2017)
Письменна Т. В. Теоретичне підґрунтя функціонування і вітчизняна практика розвитку страхового ринку. Досліджено дефініцію страхового ринку з різних наукових позицій. Розглянуто інфраструктуру страхового ринку та визначено місце кожного суб’єкта на ньому. З’ясовано суть страхового продукту для обґрунтування його ролі в організації страхових правовідносин. Встановлено основні показники, які характеризують стан і розвиток страхового ринку України, та проаналізовано окремі з них. Окреслено проблеми у функціонуванні вітчизняного страхового ринку. Визначено стратегії посткризового розвитку страхового ринку України. Письменная Т. В. Теоретические основы функционирования и отечественная практика развития страхового рынка. Исследована дефиниция страхового рынка с разных научных позиций. Рассмотрена инфраструктура страхового рынка и определено место каждого субъекта на нем. Выяснена суть страхового продукта для обоснования его роли в организации страховых правоотношений. Установлены основные показатели, которые характеризируют состояние и развитие страхового рынка Украины, и проанализированы отдельные из них. Очерчены проблемы в функционировании отечественного страхового рынка. Определены стратегии посткризисного развития страхового рынка Украины. Pysmenna T. The theoretical basis of functioning and national practice of development of insurance market. Introduction. The modern development of the national insurance market in the greatest extent is determined by economic and social factors. Obvious are problems in the functioning of the insurance market of Ukraine. To eliminate them first of all it is necessary to investigate these problems from theoretical and practical aspects. Purpose. The purpose of scientific research is substantiating theoretical bases of functioning the insurance market and analysis of the national practices of it development. Results. The definition of the insurance market from different scientific positions is investigated. The insurance market infrastructure, which included subjects of insurance, mediation, supervisory, other activities, insurance product and its consumers, is determined. The changes in the state and development of the insurance market of Ukraine through the share insurance premiums in GDP, amount of insurance premiums and insurance payments, level of insurance payments, the structure of net insurance premiums and insurance payments are appreciated. Established that in post-crisis period must implement a strategy of modernization of the insurance market, which has advantages compared with the strategy of it inertia development. Conclusion. By results of scientific research are done conclusions of theoretical and practical content. First, the insurance theory is developed in parts of formulation of essence of insurance market and determination of its infrastructure. Second, the analysis of national insurance practices showed that the pre-crisis values of basic indicators of functioning of insurance market are recovered for several years. Third, in post-crisis period it is necessary to develop and realization the strategy of development of insurance market of Ukraine.